2014
DOI: 10.1080/07481187.2014.975869
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, Continuing Bonds, and Complicated Grief Following Violent Loss: Testing a Moderated Model

Abstract: There is increasing consensus that mourners' general attachment security and ongoing sense of connectedness to the deceased figure prominently in adjustment to bereavement. However, the interplay between these variables has not been investigated thoroughly. We therefore studied 195 young adults who were bereaved by violent causes (homicide, suicide, and fatal accidents) in the previous 2 years, measuring their attachment-related insecurities (anxiety and avoidance), their specific ongoing attachment or "contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 50 publications
3
51
1
Order By: Relevance
“…However, coping post-trauma often involves rebuilding assumptions about the world (Janoff-Bulman 2002), a process in which faith traditions and spiritual practices can play a key role (ter Kuile and Ehring 2014). What often results is a push-pull paradox of traumatic grieving (Spencer-Thomas 2013) where the bereaved feel a disrupted attachment to the deceased (Currier et al 2015a).…”
Section: Spiritual Issues Are Connected To Suicide Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…However, coping post-trauma often involves rebuilding assumptions about the world (Janoff-Bulman 2002), a process in which faith traditions and spiritual practices can play a key role (ter Kuile and Ehring 2014). What often results is a push-pull paradox of traumatic grieving (Spencer-Thomas 2013) where the bereaved feel a disrupted attachment to the deceased (Currier et al 2015a).…”
Section: Spiritual Issues Are Connected To Suicide Lossmentioning
confidence: 99%
“…Out of this new paradigm emerged an appreciation of continuing bonds between the deceased and the bereaved. Some have described the continuing bonds experience as existing on two levels (Currier et al 2015a;Gee 2009). The first level is an internal representation related to memories, such as evoking a feeling of connection with the deceased by reminiscing or reflection (Harper et al 2011).…”
Section: Spiritual Experiencesmentioning
confidence: 99%
“…Despite much theorizing about the relationship between attachment style and bereavement outcome, comparatively few studies have directly examined this association. These studies have generally found a relationship between anxious attachment and worse bereavement outcomes, including PGD (Currier et al, 2015;Field and Sundin, 2001;Fraley and Bonanno, 2004;Meier et al, 2013;Wayment and Vierthaler, 2002;Wijngaards-de Meij et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, aversive thoughts and imagery related to the death event may foster negatively-valenced meaning making resulting in higher scores on the emptiness and meaninglessness subscale of the GMRI. Finally, scholars have suggested that the cognitive association between the distressing nature of the violent death story and the mental representation of the deceased may cause the bereaved to avoid engaging in a meaningful symbolic relationship with the deceased (Currier, Irish, Neimeyer, & Foster, 2015; Meier, Carr, Currier, & Neimeyer, 2013; Rubin, Malkinson, & Witztum, 2012; Rynearson & Salloum, 2011), which could disrupt meaning making related to the continuing bonds subscale of the GMRI. Accordingly, this study tests the hypothesis that violent loss fosters higher levels of PGD symptomatology in the first two years of bereavement by disrupting meaning associated with the sense of peace and continuing bonds subscales of the GMRI while exacerbating negative appraisals associated with the emptiness and meaninglessness subscale.…”
mentioning
confidence: 99%